Origins of the Unemployment Rate: The Lasting Legacy of Measurement without Theory - Card, David (American Economic Review, 2011)
The modern definition of unemployment emerged in the late 1930s from research conducted at the Works Progress Administration and the Census Bureau. According to this definition, people who are not working but actively searching for work are counted as unemployed. This concept was first used in the Enumerative Check Census, a follow-up sample for the 1937 Census of Unemployment, and continued with the Monthly Report on the Labor Force survey, begun in December 1939 by the Works Progress Administration. A similar definition is now used to measure unemployment around the world.